2014
DOI: 10.1186/1476-511x-13-102
|View full text |Cite
|
Sign up to set email alerts
|

Compared with the intake of commercial vegetable juice, the intake of fresh fruit and komatsuna (Brassica rapa L. var. perviridis) juice mixture reduces serum cholesterol in middle-aged men: a randomized controlled pilot study

Abstract: BackgroundVegetables and fruits are rich in vitamins, minerals and, dietary fiber and contribute to the prevention and improvement of obesity and metabolic syndrome. However, inadequate intake of vegetable and fruit is a concern in Japan.We therefore produced a juice mixture of fresh fruit and komatsuna (Brassica rapa L. var. perviridis: B. rapa) with the aim to investigate the effects of this juice mixture on anthropometric data, blood parameters, and dietary intake differences.MethodsThis study was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 20 publications
1
14
1
Order By: Relevance
“…The differences in PLD primary structure and isoforms contribute to the different enzymatic properties (Ruelland et al, 2015). The high amount of vegetable fiber in Komatsuna may also be the reason for the different results (Aiso et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences in PLD primary structure and isoforms contribute to the different enzymatic properties (Ruelland et al, 2015). The high amount of vegetable fiber in Komatsuna may also be the reason for the different results (Aiso et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…It is a common and popular leafy vegetable in the Japanese diet. Komatsuna contains low energy and high nutrient components that are highly effective in reducing serum cholesterol (Aiso et al, 2014). Moreover, the PL content of Komatsuna is high in the genus Brassica (Tanaka et al, 2012), and the hydrolysis of endogenous PLs such as PC by PLD is suggested to be triggered during grinding, increasing the amount of PA. On the other hand, knowledge of the lipid signaling targets and their physiological consequences in plants is limited (Hou et al, 2016), and the mechanism responsible for the abundant PA observed in mashed foodstuff is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous human intervention studies with broccoli sprouts, Brassica extracts or mixed vegetable interventions that include crucifers have reported a reduction in LDL‐C . Furthermore, transfer of sheep from grazing grass to Brassica forage results in a reduction in plasma cholesterol .…”
Section: Discussionmentioning
confidence: 98%
“…Human intervention studies have provided evidence that diets rich in cruciferous vegetables may modify plasma lipid and cholesterol profiles . At a population level, a 1% reduction in LDL‐cholesterol (LDL‐C) has been associated with a 1–2% reduction in risk of coronary artery disease .…”
Section: Introductionmentioning
confidence: 99%
“…In another study, the effects of a juice mixture of komatsuna and fresh fruit on serum cholesterol were investigated, and the results showed that serum TC and LDL-C were significantly reduced [69]. In addition, the effects of the fiber in fruits and vegetables in the diet were determined by Kelsay et al [70].…”
Section: Juices and Blood Lipidsmentioning
confidence: 99%